Laboratory Management Informationization System Design under Network Framework - Liu Jin; Deng Wei-Bin; Chen Jia-Jia (Institute of Advanced Engineering and Science, 2014)
Traditional artificial library management mode is exposed to great impact with the coming of network information era. Many shortages such as low library utilization rate, bad data secrecy, and large workload of management restrict the development of traditional artificial lending management. Based on software engineering’s design thought, this paper analyzes the needs in library system; module analysis method is applied to design the four modules of the system: landing, management, maintenance, and setting up. In server - client network framework, this paper designs the whole library informationization system. The whole system improves lending process, reduces workload, enhances safety confidentiality, and strengthens library management.